2009
DOI: 10.1016/j.jmatprotec.2008.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Improving sinterability of ceramics using hybrid microwave heating

Abstract: Microwave processing, as a new method for sintering ceramics, has key advantages such as increased heating rate, uniform heating and reduced cost compared to conventional methods. It is generally accepted that microwave sintering can improve the macroscopic mechanical performances of ceramics, however, the performances of microwave sintered ceramics on the microscopic scale are rarely investigated. In the 2 present study, the ceramics are sintered by hybrid microwave sintering (HMS), which combines the charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 13 publications
(16 reference statements)
0
21
0
Order By: Relevance
“…Additionally, the SiC had been used as a susceptor in many hybrid microwave sintering studies where room-temperature-transparent materials were successfully heated (Zhao et al, 2000;Huang et al, 2009;Brandão et al, 2012). Tubular susceptor had probably correcting effect to the inhomogeneous electromagnetic field, so that the sample was heated more uniformly without hot spots which could cause partial melting of samples in early stage.…”
Section: Conversion Of Spodumene In Microwave Furnacementioning
confidence: 99%
“…Additionally, the SiC had been used as a susceptor in many hybrid microwave sintering studies where room-temperature-transparent materials were successfully heated (Zhao et al, 2000;Huang et al, 2009;Brandão et al, 2012). Tubular susceptor had probably correcting effect to the inhomogeneous electromagnetic field, so that the sample was heated more uniformly without hot spots which could cause partial melting of samples in early stage.…”
Section: Conversion Of Spodumene In Microwave Furnacementioning
confidence: 99%
“…Figures 19a, b show the comparison of thermal residual stress distributions and Vickers Hardness distribution of microwave and conventionally sintered samples. 183 The thermal residual stress investigation shows that the microwaves can sinter ceramics in entire volume, resulting in improved mechanical properties. The micro hardness test on microwave-sintered specimen finds superior mechanical properties compared to conventionally sintered specimen.…”
Section: Ceramic Processingmentioning
confidence: 99%
“…The micro hardness test on microwave-sintered specimen finds superior mechanical properties compared to conventionally sintered specimen. 183 Similarly, microwave sintering of calcium phosphate ceramics (hydroxyapoatite and tri-calcium phosphate) were carried out using a 3 kW microwave system operated at a frequency of 2.45 GHz. It was found that the samples sintered by microwave at 1250 C for 30 minutes had high density and homogeneous microstructure for all compositions.…”
Section: Ceramic Processingmentioning
confidence: 99%
“…After this research, a lot of work was carried out in this field of metallic powder processing [8][9][10][11], but still processing of bulk metals was unsuccessful due to the lower depth of penetration of microwaves in the metals, which often causes reflection of microwaves and plasma formation. Further, researchers [12][13][14] focused on hybrid heating systems to couple the metals with microwaves, such that the initial heating of metals by microwaves increases the depth of penetration and causes heating of metallic materials. The successful processing of bulk metallic material in the form of joining of metallic material was carried out by Sharma et al [15] in the year 2009, by using the domestic microwave applicator and principles of microwave hybrid heating.…”
Section: Introductionmentioning
confidence: 99%